Context matters: How smartphone (mis)use may disrupt early emotion regulation development. (January 2022) - Roberts, Max Z.; Flagg, Amanda M.; Lin, Betty
Abstract: Smartphones are prevalent across society. Substantial literature has highlighted risks of smartphone use for children under three years of age. Nonetheless, recent surveys suggest that young children use smartphones regularly. Therefore, understanding the associated developmental risks remains pivotal. Most research has examined what children do on their phones, and how long they use them, as keys to understanding risk. We additionally highlight that the contexts in which smartphones are used provide another lens through which to evaluate and mitigate smartphone use risk. In some contexts, for example, smartphones could interfere with developing early emotion regulation competencies. We describe smartphone interference in emotion regulation development using Morris et al.'s (2007) tripartite model of familial influence, to demonstrate incorporating contextual perspectives of developmental smartphone interference. Additionally, the existing literature highlights SES disparities in smartphone use trends and for emotion regulatory functions that warrant greater attention. Clinical and research implications will be discussed.